A3.11 Endothelin-1 directly induces a profibrotic phenotype both in human dermal microvascular endothelial cells and skin fibroblasts. (13th February 2015) - Soldano, S; Montagna, P; Brizzolara, R; Sulli, A; Cutolo, M
Abstract : Background and objectives: Endothelial cell activation and dysfunction contribute to vascular damage, which represents an early event in fibrotic diseases, including systemic sclerosis (SSc). 1 These activated cells secrete several mediators including endothelin-1 (ET-1) and transforming growth factor-β1 (TGFβ1). 2 In SSc, myofibroblast activation and their overproduction of profibrotic molecules, such as fibroblast specific protein-1 (S100A4), α-smooth muscle actin (α-SMA), fibronectin (FN) and type I collagen (COL1) were known to characterise the late phase of fibrotic process. To investigate the involvement of ET-1 and TGFβ1 on microvascular alteration through the directly induction of profibrotic molecules S100A4, α-SMA and FN in cultured human dermal microvascular endothelial cells (HMVECs). In addition, the effects of ET-1 in inducing SSc myofibroblasts phenotype were also investigated in cultured normal skin fibroblasts. Materials and methods: HMVECs were treated for 6 days with or without ET-1 (100nM) and TGFβ1 (10ng/ml). Cultured normal and SSc skin fibroblasts were isolated from ten SSc patients (mean age 65 ± 7 years) who fulfilled the new criteria of EULAR/ACR 3 and five age matched healthy subjects after signing an Informed Consent and Ethical Committee. Cultured normal fibroblasts were treated for 48 h with or without ET-1. Untreated cultured SSc fibroblasts were used as positive controls. S100A4, α-SMA and FN protein synthesis and expression were evaluated by immunofluorescence, immunocytochemistry and quantitative real time in HMVECs. α-SMA, COL1 and FN were evaluated by immunofluorescence, immunocytochemistry, and western blotting in cultured fibroblasts. Statistical analysis was performed by non-parametric Mann-Whitney test. Results: In HMVECs, qRT-PCR showed that ET-1 and TGFβ1 were able to significantly up-regulate the gene expression of S100A4, α-SMA (p < 0.01 for both proteins) and FN (p = 0.01; p = 0.04) compared to untreated cells. Results were confirmed by immunofluorescence and immunocytochemistry. In cultured normal skin fibroblasts, ET-1 induced the expression of α-SMA leading to the myofibroblast phenotype activation similar to that observed in SSc fibroblasts. In cultured normal fibroblasts ET-1 significantly increased both COL1 and FN synthesis compared to untreated cells (p < 0.01 for both). The synthesis of these ECM protein was similar to that observed in SSc fibroblasts. Results were confirmed by Western blotting. Conclusion: Present results seem to suggest a possible direct action of ET-1 both in the early and late phase of fibrotic process, inducing endothelial cell activation and production of a pro-fibrotic microvascular environment, as well as determining myofibroblast activation and their ECM overproduction. References: Wynn TA, Ramalingam TR. Mechanisms of fibrosis: therapeutic translation for fibrotic disease. Nat Med 2012;18:1028–40. Iglarz M, Clozel M. At the heart of tissue: endothelin system and end-organ damage. Clin Sci 2010;119:453–63. van den Hoogen F, Khanna D, Fransen J, et al . 2013 classification criteria for systemic sclerosis: an American College of Rheumatology/European League against Rheumatism collaborative initiative. Arthrit Rheum 2013;65:2737–47.